Carbon sources as factors affecting the secondary metabolism of the maize pathogen Fusarium verticillioides - Achimón, Fernanda (2019)
Fusarium verticillioidesis a fungal pathogen of maize and a prolific producer of fumonisin B1(FB1), which has encouraged the search of analytical methods for FB1 detection during grain storage.Secondary metabolites(FB1 and sesquiterpenes) are synthetized from precursors derived from primary metabolism, which is strongly affected by carbon sources. The purpose of our study was to evaluate the effect of different carbohydrates on vegetative growth, conidiation and secondary metabolism in F. verticillioides. We observed lower values of lag period in cultures with amylopectin, amylose and starch (0.06 ± 0.01, 0.18 ± 0.01 and 0.26 ± 0.00 day,respectively), along with elongated hyphae. Besides, amylose and maltose stimulated fungal growth(5.50 ± 0.01 and 5.23 ± 0.01 mm/day, respectively) and conidiation (13.75×105± 0.58×105 and 13.49×105± 0.38×105conidia/ml).Furthermore,maximum production of FB1 was achieved with glucose(4.4×103±0.18×103μg/g DW), while sesquiterpene production was higher with amylopectin(158.5×10−12± 8.80×10−12μg/g DW), highlighting the complex mechanisms that regulate fungal secondary metabolism. Finally, we proposed a sesquiterpene profile that couldbe used as a volatile biomarker of FB1 contamination in stored maize kernels.